Seismic reliability of continuously supported steel wine storage tanks retrofitted with energy dissipation devices. (1st September 2015) - Colombo, J.I.; Almazán, J.L.
Highlights: The seismic reliability of two typical wine storage tanks was evaluated. Using metallic dampers may reduce the limit state probability in the order of 80%. A simplified stress verification for the tank-damper connection was performed. Abstract: Seismic protection of wine storage tanks has become a very important issue due to the booming of the wine industry in seismic countries such as the US, Italy, New Zealand, Chile and Argentina. In order to improve the seismic reliabilities of structures, external energy dissipation may be used beneficially. In this study, the reliabilities of two continuously supported cylindrical steel tanks (one slender and one broad), used for fermentation and wine storage, with and without an external energy dissipation system are calculated by using simulation. A group of non-linear time history analyses is established in order to assess the influence of the energy dissipation system. Each non-linear time history is obtained by means of a mathematical model that considers the fluid–structure–soil interaction. A set of different seismic ground motions is used for the purpose of obtaining robust results in the reliability analysis. Finally, the seismic reliability analysis shows that, for steel wine storage tanks, an external energy dissipation system would reduce the limit state probability in the order of 80%.